EVALUATION OF PERFORMANCE FOR CARAWAY (Carum carvi L.) CULTIVARS OVER IRAQI ENVIRONMENTS - Almehemdi, A. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Assessment of genetic diversity for various traits would contribute in hybridization projects in order to recover aspired recombinants. Therefore, metroglyph analysis and ANOVA were conducted out to estimate genetic diversity among seven caraway genotypes. Field experiment was applied in winter season of 2011/2012 with three replicates. Consequently, data were recorded on plant height, branches no., umbels no. umbels diameter, no. of umbellets and plant yield. Results showed that allotting of index scores for each trait of seven caraway genotypes represented the worth of the genotype in respects to the trait which the performance of genotype is represented by total index score for all traits of that genotype. Thus, Bery and Mosul genotypes ascertained the highest index scores of 16, for each one. Moreover, Metroglyph scatter diagram revealed three groups of caraway genotypes. Therefore, it could be concluded that metroglyph technique simply classified genotypes to groups and had potentiality to interpret genotypes performance regarding the index scores. Thus, it could be recommended to apply crossing or hybridization between individuals from different groups alternatively to individuals from same group. Genotypes of Bery, Mosul, Sury and selectedF1 (Group2), and Balady (Group3) were distinct which possible to apply crossing between one of group2 individuals with another one of group3.